(untitled) (Research, Society and Development, 2020)
Currently research focused on the area of teaching Chemistry has sought strategies and tools to improve the students’ learning process. The use of playfulness has been one of the resources widely used by researchers and teachers in the classroom. When choosing games as an evaluative tool, the teacher can find it easier to identify students’ difficulties, in addition to relaxing the way students are evaluated. The objective of this study was to develop a didactic game with the purpose of teaching the content of "collective properties", justifying it by the lack of games and research aimed at teaching Physics-Chemistry of Solutions. After construction, the game was applied to two classes in the second year of high school, in two different schools. In order to evaluate the application of the game, semi-structured questionnaires were used, which contained questions about the students’ opinion about the use of didactic resources, such as the educational game. Through the analysis of the questionnaires answered by the students, it can be verified that after using the game, there was progress in the constitution of their knowledge, in addition to confirming that they approved the use of this resource in the teaching of collective properties. From this research it can be concluded that games are a great choice to be used in classes, being valid as a didactic resource, as it stimulates, motivates students, increases concentration and promotes group discussions and interactions. Al elegir los juegos como herramienta de evaluación, el maestro puede encontrar más fácil identificar las dificultades de los estudiantes, además de relajar la forma en que los estudiantes son evaluados.